2021
DOI: 10.3390/plants10091823
|View full text |Cite
|
Sign up to set email alerts
|

The Basis of Tolerance Mechanism to Metsulfuron-Methyl in Roegneria kamoji (Triticeae: Poaceae)

Abstract: Roegneria kamoji, a perennial monocot weed that belongs to the tribe Triticeae (family: Poaceae), is an emerging problematic weed in winter wheat (Triticum aestivum) fields in China. We have previously confirmed four R. kamoji populations tolerant to acetyl-CoA carboxylase (ACCase) inhibitors, and failed control of these populations by metsulfuron-methyl was observed. The objective of this study was to characterize the level of tolerance to metsulfuron-methyl, the basis of tolerance mechanism, and cross-tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Mesosulfuron‐methyl resistance has evolved in 27 weed populations, bispyribac‐sodium resistance in 14 weed populations, and pyriminobac‐methyl resistance in two weed populations (Heap, 2023). Although metabolic resistance to mesosulfuron‐methyl and/or bispyribac‐sodium has been implicated in a few weedy species (Huang et al., 2019; Iwakami, Uchino, et al., 2014; Riar et al., 2013; Tang et al., 2021; Yu et al., 2021; Zhao et al., 2017), the only gene identified to be involved in mesosulfuron‐methyl resistance is CYP709C56 in A. aequalis CYP709C56 (Zhao et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mesosulfuron‐methyl resistance has evolved in 27 weed populations, bispyribac‐sodium resistance in 14 weed populations, and pyriminobac‐methyl resistance in two weed populations (Heap, 2023). Although metabolic resistance to mesosulfuron‐methyl and/or bispyribac‐sodium has been implicated in a few weedy species (Huang et al., 2019; Iwakami, Uchino, et al., 2014; Riar et al., 2013; Tang et al., 2021; Yu et al., 2021; Zhao et al., 2017), the only gene identified to be involved in mesosulfuron‐methyl resistance is CYP709C56 in A. aequalis CYP709C56 (Zhao et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…), an annual grass weed of the family Triticeae, is tolerant to most herbicides in wheat, and mesosulfuron-methyl is the only wheat-registered herbicide that provides effective control of this weed in China [29]. In our previous studies, R. kamoji showed a response pattern to all foliar-applied AC-Case-and ALS-inhibiting herbicides that was similar to that shown by wheat [3,4]. The results of this study indicated that R. kamoji also exhibited a similar response to the PRE herbicides chlorotoluron and diflufenican, and only buatchlor provides relatively higher control for R. kamoji while having no impact on the seedling emergence of wheat.…”
Section: Discussionmentioning
confidence: 84%
“…The rhizome of this population was separately cultivated in a greenhouse at China National Rice Research Institute (CNRRI, 30.04 N, 119.55 E), and seeds collected in 2020 were used in this study. Details of this population can be found in our previous studies [3,4]. Wheat seeds of the variety Yangmai 25 were purchased from China National Seed Group Co. Ltd. (Beijing, China).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation